Global Culture: Discursive and Social Practices - Tanatova, Dina; Yudina, Tatyana (Slavica, 2020)
The dynamics of modern society development is directly proportional to changes in its culture. In the discourse of global culture, there are many supporters of its real presence, and many opponents who claim that such a phenomenon does not exist in principle. The article considers various polar points of view. Arguments are presented that confirm the existence of a global culture formed as a result of multiple cultural contacts, including cultural tourism. Digitalization has become a new impetus for the development of global culture, which has large-scale ways to spread the achievements of world culture in General, and art in particular, to the population of the planet, regardless of location. Digital formats have proven their worth in specific social practices.